INVESTIGATING THE HISTORICAL COURSE OF ANCIENT GYMNASIUM SPORTS IN ANCIENT IRAN - Azizi, Bisotoon; Mohammadi, Mohammad (Revista Prâksis, 2024)
Sports have been an integral part of culture in most ancient civilizations such as Iran, Greece and Egypt. In Iranian literature, both before Islam and after, there are stories of epic makers and epic makers. The first view has a history that is like this. As long as the history of Iran and the people of Iran does not consider a lifetime of more than three hundred years for the ancient and heavy lifting sport and the second point of view, for the formation of gymnasium and heavy lifting sports. The purpose of this research is to review the historical course of ancient gymnastics in ancient Iran. The research method was library-type among about 200 related sources, of which 34 more reliable and close sources were identified and studied. In this regard, the researcher sought to find the history and formation of the ancient sport of gymnastics in ancient Iran.